APPLYING THE 3R PRINCIPLES FOR SUSTAINABLE WASTE MANAGEMENT IN CIBODAS TOURISM VILLAGE - Kuswanto, Arif; Madiawati, Putu Nina; Nurnida, Ida (Jurnal Pengabdian Indonesia (JPI), 2026)
The community service program implemented in Cibodas Tourism Village, Pasirjambu District, Bandung Regency, aimed at improving local waste management practices, reducing environmental impacts of tourism, and creating livelihood opportunities through circular-economy activities. The program combines participatory methods and workshops on waste management by applying the 3R principles (Reduce, Reuse, and Recycle). Measurable outcomes included improved source segregation accuracy, an operational community composting facility, and income streams from recyclable materials. The initiative, aligned with Sustainable Development Goals (SDG), demonstrates that integrated education and infrastructure interventions can produce environmental and socio-economic co-benefits in rural tourism settings.